Nonlinear dynamical response of sinusoidal impulsive actuated piezoelectric/porous sandwich nanoharvesters via GM-based meshfree collocation formulations - Sahmani, Saeid; Safaei, Babak; Fan, Fan (Pergamon-Elsevier Science Ltd, 2024)
In this paper a new effective computational approach based upon a meshless collocation formulation of the Gurtin-Murdoch (GM) continuum elasticity is described. The newly developed computational model for the third-order shear flexible elastic plates is then employed to analyze the nonlinear dynamical response of piezoelectric/porous sandwich nanoharvesters subjected to a sinusoidal impulsive actuation. The material properties relevant to the porous passive core having uniform or two graded through thickness porosity dispersions are estimated using the approach of Gaussian random field. The weak form of model conception is discretized and solved numerically via employing an incorporation of the polynomial and radial basis functions having the capability to remove any feasible singularity as well as taking more precise approximation into account within the GM-based meshfree collocation formulations. It is deduced that by contemplating the surface stress tensor via the established GM-based model, the achieved voltage from the sinusoidal impulsive actuated sandwich nanoharvesters reduces, especially for those possessing lower thickness. Also, it is deduced that for the fully simply supported impulsive actuated sandwich nanoharvester, by changing the porosity decoration of distribution from the uniform decoration to FGO and FGX graded ones, the significance of the role of surface stress tensor in the achieved voltage reduces from 12.45% to 12.28%, and enhances from 12.45% to 12.64%, respectively. For the fully clamped impulsive actuated sandwich nanoharvester, by changing the porosity decoration of distribution from the uniform decoration to FGO and FGX graded ones, the significance of the role of surface stress tensor in the achieved voltage reduces from 15.01% to 14.68%, and enhances from 15.01% to 15.37%, respectively.
Keywords: Nonlinear dynamic response; Nanomechanics Meshless formulations; Energy harvesting; Porous/piezoelectric composites